Kontribusi Nilai-Nilai Thariqat Naqshabandiyah pada Pembinaan Akhlak Santri Pondok Pesantren Darul Muta’allimin Kabupaten Aceh Singkil - Haiyan Haiyan; Mukhsin Nyak Umar; Yusra Jamali (Tadabbur: Jurnal Peradaban Islam, 2023)
This article aims to describe the contribution of the values of Tariqat Naqshabandiyah in fostering the morals of students at the Darul Muta'allimin Islamic Boarding School, Aceh Singkil District. To describe the problem in depth and thoroughly, the researcher used a qualitative descriptive method, then the data was described, analyzed and discussed to answer the problem. From the results of the study it was found that students and congregations from the community who had attended khalwat suluk argued that practicing the Naqsayabandiyah Order could change their behavior in a better direction and welcomed the khalwat suluk worship held at the Darul Muta'allimin Islamic Boarding School in Aceh Singkil, where the goal is to get closer to Allah, is good and does not interfere, because the social relations of the khalwat congregation with the community are maintained, because the purpose of suluk activities in the Naqsyabandiyah Tariqat is noble to get the pleasure of Allah swt. so the benefits are peace of mind, always remembering Allah's commands and all His prohibitions, so that students and residents consider this activity very positive, because all things that have a good purpose to get closer to Allah will get good results too.